Enhanced switch combining for spatial diversity with a switch window over correlated Nakagami‐m fading channels. (20th February 2012) - Chau, Yawgeng A.; Chen, Yao‐Hua
SUMMARY: On the basis of a mixture of the selection combining and switch‐and‐stay combining schemes, the enhanced switch combining (ESC) scheme is proposed for antenna diversity over multiple correlated Nakagami‐ m fading channels, where a switch window with upper and lower switch thresholds are used. Compared with the existing select‐and‐stay combining or switch with post‐examining, the ESC scheme reduces simultaneous multiantenna observations and hence saves processing time and energy from multibranch observations, while achieving matched receiver performance. Thus, ESC also has better performance than switch‐and‐examine combining (SEC). To assess the reduction of simultaneous observations, a dual‐observation rate is defined. Moreover, the ESC unifies some well‐known switch‐based combining schemes (for example selection combining, switch‐and‐stay combining, or SEC) in the sense that, by adjusting switch thresholds, these combining schemes become different special cases of ESC. The CDF, PDF, and moment generating function of the combined signal‐to‐noise ratio for ESC are derived for general fading channels. Then, the outage probability and the average BER of different binary modulations over correlated Nakagami‐ m fading channels are evaluated. Numerical results from analysis and simulation are presented to demonstrate ESC performance. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Based on a mixture of selection and switch‐and‐stay combining schemes, a new switch combining scheme is proposed for antenna diversity over multiple correlated Nakagama‐ m fading channels, where a switch window with upper and lower switch thresholds are used. Compared to existing switch‐based schemes, the proposed scheme reduces simultaneous multi‐antenna observations and hence saves processing time and energy from multi‐branch observations, while it can achieve matched receiver performance. To assess the reduction of simultaneous observations, a dualobservation rate is defined. Moreover, the proposed combining scheme unifies some well‐known switch‐based combining schemes in the sense that, by adjusting the two switch thresholds, the existing combining schemes become different special cases of the proposed scheme. For performance evaluation, the outage probability and the average bit error rate of different binary modulations over correlated Nakagami‐ m fading channels are derived.